Studi Numerik Perbandingan Perilaku Struktur Auxetic Chiral dan Honeycomb Pada Pembebanan Tekan dan Impact - Simon Sindhu Hendradjaja; Algazali, Febri; Syarifah Fairuza; Budi Aji Warsiyanto; Riskha Agustianingsih (Jurnal Teknologi Kedirgantaraan, 2025)
This study aims to compare the structural performance of auxetic chiral and honeycomb sandwich panels under compression and impact loading to identify their potential application in lightweight aerospace structures. Numerical simulations were conducted using the ABAQUS platform to analyze the mechanical response and failure behavior of both core designs. A mesh convergence study was performed to ensure accurate and reliable simulation results. The impact tests were conducted at energy levels of 5 J, 10 J, and 20 J, while compression tests were applied with a displacement of 4 mm. The results show that the auxetic chiral core demonstrates superior performance compared to the honeycomb core by achieving smaller deformations and better energy absorption under equivalent impact forces. Furthermore, the auxetic chiral core exhibits a higher compressive strength of up to 111 MPa, outperforming the honeycomb core, which withstands only 50 MPa. Failure analysis also reveals that facesheets on auxetic panels experience significantly smaller damage areas compared to honeycomb panels. These findings indicate that auxetic chiral cores offer promising advantages for designing lightweight, impact-resistant aerospace structures.